Elevated Thresholds for Light Touch in Children With Autism Reflect More Conservative Perceptual Decision-Making Rather Than a Sensory Deficit - Quinde-Zlibut, Jennifer M.; Okitondo, Christian D.; Williams, Zachary J.; Weitlauf, Amy; Mash, Lisa E.; Heflin, Brynna H.; Woodward, Neil D.; Cascio, Carissa J. (Frontiers in Human Neuroscience, 2020)
Individuals with autism spectrum disorder (ASD) are often behaviorally hyper-reactive to light touch, but it is unclear to what degree this arises from a fundamental sensory difference versus higher order systems for attention or emotion processing. Thus far, experimental findings for light touch detection are mixed, and few previous studies have independently considered sensitivity (the ability to discriminate signal from noise) and decision criterion (the overall response bias or tendency to answer ‘yes’ or ‘no’ in a detection task). We tested a large sample of children, adolescents, and adults with ASD (n=88) and with typical development (n=59) using von Frey filaments to derive light touch thresholds at the palm. We calculated signal detection metrics for sensitivity (Az) and response criterion (c) from hit and false alarm rates. Both metrics exhibited significant group differences, such that the ASD group was less sensitive, but had a much more conservative response criterion. We used a best subset model selection procedure in three separate ordinal regressions for the whole group, adults, and children adolescents. In all selected models, c was by far the most significant predictor of threshold, supplanting effects of diagnostic group that were significant in the baseline models. In contrast, Az was not a significant predictor of threshold in any of the models. Mean values of c were similar for adults with and without autism and for children/adolescents with ASD, but lower (more liberal) in children/adolescents with TD. This suggests that children with ASD exhibit a conservatism in their perceptual decision-making that differs from their TD peers but resembles that of adults. Across the sample, the value of c was significantly and positively correlated with age and with autism symptoms (SRS-2 total score), in addition to thresholds. The results of this study suggest that, rather than a sensory difference in detection of light touch, there is a difference in response bias such that children with ASD are more conservative/likely to report ‘no’ if unsure, than their young TD peers. Future work should consider the implications of conservative response criterion in ASD for commonly used forced-choice psychophysical paradigms.